2018
DOI: 10.1002/pssa.201700427
|View full text |Cite
|
Sign up to set email alerts
|

InP:S/AlInAs:C Tunnel Junction Grown by MOVPE for Photovoltaic Applications

Abstract: Multijunction solar cells based on III-V compounds are one of the most effective possibilities to achieve high efficiencies for space and terrestrial applications. In this work, AlInAs:C/InP:S tunnel junctions are fabricated using MOVPE. Type-II interface band alignment of AlInAs/InP heterostructure is ideal for increasing the photogenerated carriers tunneling. Furthermore, wide bandgaps ensure a high transmission of the incident light. The J-V characteristics of the final devices show very good results in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The growth temperatures were 630 °C for the n-type layers and 600 °C for the p-type layers. The growth conditions for the tunnel junction are somewhat different from the rest of the cell and they have been thoroughly described elsewhere [29]. The InP/AlInAs tunnel junction allows to reach a high peak tunneling current of 1570 A/cm 2 at voltages between 120 mV and 160 mV, thus suggesting very low losses under tandem cell operation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth temperatures were 630 °C for the n-type layers and 600 °C for the p-type layers. The growth conditions for the tunnel junction are somewhat different from the rest of the cell and they have been thoroughly described elsewhere [29]. The InP/AlInAs tunnel junction allows to reach a high peak tunneling current of 1570 A/cm 2 at voltages between 120 mV and 160 mV, thus suggesting very low losses under tandem cell operation.…”
Section: Methodsmentioning
confidence: 99%
“…We have first fabricated and characterized the two single junction cells (SJCs) grown on InP substrates. Then, we have combined them into a tandem device fabricated on an InP substrate, by including an intermediate, transparent InP/ AlInAs tunnel junction previously presented in [29].…”
Section: Introductionmentioning
confidence: 99%
“…InP:S-based solar devices have been reported in the literature. In particular, Faur et al [16] reported a p + n (Cd,S) heterojunction InP solar cells for space applications and a InP:S/AlInAs:C tunnel junction, presented by the III-V Lab group [17], has been successfully produced and used to fabricate InP/ InGaAs tandem solar cells [18].…”
Section: Introductionmentioning
confidence: 99%